Penggunaan Metode Team Quiz Sebagai Upaya Meningkatkan Minat dan Hasil Belajar Siswa Pada Mata Pembelajaran PAI Kelas III SDN 1 Sampang - Zainul Fahmi; Siti Fatimah; Imam Subarkah (IAINU Kebumen, 2023)
This research is a Classroom Action Research (CAR) using the team quiz method. This is done so that students can increase their interest, especially in the PAI subject. After that, it is hoped that after completing the lesson by applying the team quiz model, researchers will notice an increase in student interest as indicated by an increase in student learning outcomes at SDN 1 Sampang, especially in class III. This research was conducted with the Class Action Research (CAR) method, which is an effort to increase student interest in PAI subjects. The process of collecting data with technical observations between teachers and students. Student. The results showed that: The use of the team quiz method can improve student learning outcomes. This can be seen from the results of the analysis in cycle I and cycle II, showing an increase in student learning mastery in cycle II. This result is clearly seen from the average student learning outcomes in the first cycle with a percentage of 70.47% while in the second cycle the percentage is 87.62%. This proves the mastery of student learning has increased in cycle II. The use of the team quiz method in PAI and BP subjects can increase students' interest in learning which can be seen from the activeness of students answering questions, asking questions if they do not understand the material, listening to teacher explanations, and participating in team quiz activities with enthusiasm. Based on this research, it was concluded that there was an increase in students' interest in learning in PAI and BP subjects using the team quiz method.